Does tour quality impact tourist satisfaction? Experiences from Arunachal Pradesh, India - Mudang Tagiya; Odang Mara (Business Analyst)
Purpose – This study addresses a critical aspect of tourism in Arunachal Pradesh, India, by investigating how tour quality impacts on tourist satisfaction of domestic tourists. As one of the least explored regions of the country, Arunachal Pradesh holds immense tourism potential. Understanding the factors that contribute to tourist satisfaction, particularly the role of tour quality, is of paramount importance for enhancing the region's appeal as a sought-after travel destination. Design/methodology/approach – The study was operationalized using survey questionnaires from domestic tourists (n = 200) visiting Ziro Valley, Arunachal Pradesh, India. A convenient sampling method was adopted for the study. Ordinary least square structural equation modeling (OLS-SEM) was used to measure the relationships. Findings – The findings show that tourist expectations and tourist motivation influence tour quality and consequently impact the overall satisfaction of tourists. Practical implications – This study extended the existing literature on tourist satisfaction in the domain of travel and tour by demonstrating the significance of tourist expectations and motivations on tour quality and tourist satisfaction. The findings offer insights for stakeholders seeking to enhance destinations' image, tour quality and overall tourist satisfaction. Originality/value – This paper provides original contributions to the field of tourism by examining the effect of tour quality on tourist satisfaction. It integrates the factors, namely tourist expectations and motivations, into the analysis, offering insights into delivering customized tour experiences that meet tourists' needs.